Essentials of political ideas - Heywood,Andrew (Palgrave, 2018)
This new textbook from best-selling politics author Andrew Heywood investigates the ideas that have dominated political thinking across the globe, and examines the different ways in which they have been interpreted and reinterpreted. Written in an accessible and engaging style, it covers the key ideological traditions, offering an exposition of their history and development, their core themes and internal divisions and their impact on contemporary political behaviour, movements, parties and governments. This new introduction is written specifically for the new A Level syllabus in Political Ideas and covers all the issues and topics in the Edexcel and AQA specifications. It includes a range of useful features to help students develop and apply their understanding of ideas, ideologies and thinkers.